2021
DOI: 10.21147/j.issn.1000-9604.2021.02.12
|View full text |Cite
|
Sign up to set email alerts
|

Combined detection and subclass characteristics analysis of CTCs and CTECs by SE-iFISH in ovarian cancer

Abstract: Objective Hematogenous metastasis is essential for the progression of ovarian cancer (OC), and circulating tumor cells (CTCs) are part of the metastatic cascade. However, the detection rate of CTC is low due to the use of less sensitive detection methods. Therefore, this study aimed to detect CTCs and circulating tumorigenic endothelial cells (CTECs) in patients with OC using subtraction enrichment and immunostaining and fluorescence in situ hybridization (SE-iFISH). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…The clinical value of CTCs in ovarian, breast, prostate and colorectal cancers has been confirmed in several studies and meta-analyses ( 5 , 7 - 13 ), with nearly thirty articles concerning the clinical application of CTCs to ovarian cancer being published in the last decade. Due to the variety of detection techniques used, the reported detection rates in these publications are variable, ranging from 12% to 100% ( 14 - 22 ). Currently, a common standard for CTC detection has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical value of CTCs in ovarian, breast, prostate and colorectal cancers has been confirmed in several studies and meta-analyses ( 5 , 7 - 13 ), with nearly thirty articles concerning the clinical application of CTCs to ovarian cancer being published in the last decade. Due to the variety of detection techniques used, the reported detection rates in these publications are variable, ranging from 12% to 100% ( 14 - 22 ). Currently, a common standard for CTC detection has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, CECs expressing endothelial markers CD105 and/or CD146 (CellSearch), have been associated with poor patient outcome in metastatic breast 32 and colorectal cancer 33 . However, only a few studies have reported CECs being detected in OC CTC studies 21 , 34 . Thus, it would be important to combine CTC and CECs analyses for prognostication in future OC studies.…”
Section: Discussionmentioning
confidence: 99%
“…We previously noted putative CTCs expressing CK/EpCAM as well as CD31 positive 18 , presenting as pseudoendothelial phenotype. Recently putative tumorigenic CECs with aneuploidy have been reported from OC 21 and lung cancer patients 22 . Thus, we aimed to evaluate the neoplastic origin of the putative CTCs identified by carrying out genetic analysis for CNAs.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, depending on the techniques used for the CTCs detection, the positivity rates documented in different studies varied from 12% to 90%. The detection rate might be even higher and reach 95%, as it was recently presented using the subtraction enrichment of the cells followed by immunostaining and fluorescence in situ hybridization [ 20 ]. It points to the importance of proper isolation methods allowing successful evaluation of ovarian CTCs.…”
Section: Biology Of Circulating Tumor Cellsmentioning
confidence: 99%
“…Haematogenous spread of cancer cells in ovarian carcinomas is believed to be a rather rare event. Still, this phenomenon is well documented [ 7 , 8 , 9 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 23 , 24 , 26 , 32 , 43 , 50 , 69 , 70 , 71 ], and the presence of CTCs in blood was recently shown to correlate with tumor stage, presence of ascites, tumor debulking, disease recurrence, shorter OS and PFS [ 7 , 18 , 23 , 24 , 43 , 50 , 69 ].…”
Section: Clinical Relevance Of Ctcs In Ovarian Cancermentioning
confidence: 99%